CSSR: Historical Reflections. (September 2021) - Gareau, Paul L
As part of the 50 th anniversary celebration of the Canadian Corporation for Studies in Religion (CCSR), this article provides a reflection on the past, present, and future of the Canadian Society for the Study of Religion (CSSR). CSSR members were given the space to outline their thoughts and experiences of over 50 years of Religious Studies in Canada. This collaborative article tracks the development of the discipline through the 1970s from theology to comparative religion, to the transformation of the 1980 -90s with an interdisciplinary and critical engagement, to the new millennium infusion of socio-political research, critical self-reflexivity, and lived religion work. We also focus on the role of the CSSR in shaping and promoting Religious Studies in Canada through its various academic activities as well as observing the fragmentation and decline of Religious Studies programs in Canadian universities. And finally, we look to the future questioning how the CSSR and Religious Studies can remain relevant against a backdrop of institutional changes due to funding austerity and the COVID global pandemic to supporting Religious Studies inside and outside of academia. This article is not intended as a detailed history of the CSSR, but an opportunity to see a representation of our experiences and hopes for Religious Studies in Canada.